Representation Of Sexual Violence Of Minors In Mass Media: Case Study Liputan6.Com - Rismawati, Rismawati; Rahmatunnair, Rahmatunnair; Suhadi, Suhadi; Kaddas, Badruddin; Suhra, Sarifa; Faizah K, Nurul (Journal of Research and Multidisciplinary, 2024)
This article discusses the representation of sexual violence against minors in the mass media, a case study of Liputan 6.com. The aspects highlighted and the framing of news about sexual violence against minors which focuses on the case of 13 female students who were abused by their own teachers in online media merdeka6.com through media text analysis framing William A. Gamson model. The research results show that Online media Liputan6.com frames news about victims of sexual violence, tends to raise the incident of sexual violence against 13 female students as something that is of great interest to the public. This incident is very unfortunate because the Islamic boarding school teachers who should be educating, looking after and protecting their female students actually commit sexual violence so that Some people no longer trust their children to study at Islamic boarding schools.